Receptor-Receptor Interactions as a Widespread Phenomenon: Novel Targets for Drug Development? - Guidolin, Diego; Marcoli, Manuela; Tortorella, Cinzia; Maura, Guido; Agnati, Luigi F. (Frontiers in Endocrinology, 2019)
The discovery of receptor-receptor interactions (RRI) has expanded our understanding of the role that G protein-coupled receptors (GPCRs) play in intercellular communication. The finding that GPCRs can operate as receptor complexes, and not only as monomers, suggests that several different incoming signals could already be integrated at the plasma membrane level via direct allosteric interactions between the protomers that form the complex. Most research in this field has focused on neuronal populations and has led to the identification of a large number of RRI. However, RRI have been seen to occur not only in neurons but also in astrocytes and, outside the central nervous system, in cells of the cardiovascular and endocrine systems and in cancer cells. Furthermore, RRI involving the formation of macromolecular complexes are not limited to GPCRs, being also observed in other families of receptors. Thus, RRI appear as a widespread phenomenon and oligomerization as a common mechanism for receptor function and regulation. The discovery of these macromolecular assemblies may well have a major impact on pharmacology. Indeed, the formation of receptor complexes significantly broadens the spectrum of mechanisms available to receptors for recognition and signaling, which may be implemented through modulation of the binding sites of the adjacent protomers and of their signal transduction features. In this context, the possible appearance of novel allosteric sites in the receptor complex structure may be of particular relevance. Thus, the existence of RRI offers the possibility of new therapeutic approaches, and novel pharmacological strategies for disease treatment have already been proposed. Several challenges, however, remain. These include the accurate characterization of the role that the receptor complexes identified so far play in pathological conditions and the development of ligands specific to given receptor complexes, in order to efficiently exploit the pharmacological properties of these complexes.